“Sorry, I’m not from here!”: Female international student-athletes’ transitions into college athletics in the United States - Swim, Nicholas; Lee, Youngjik; Hums, Mary A. (Frontiers in Psychology, 2023)
The number of NCAA international student-athletes (ISAs) on US college campuses has increased to upwards of 20,000. This current study sought to investigate their transition experiences into colleges, based on the ISA transition adjustment model. More specifically, this study sought to better understand how recent changes in the NCAA have impacted the ISA population and if the antecedent factors in the transition adjustment model (personal, inter-personal, perceptual, and cultural distance) still represent the best indicators of successful transition for ISAs. To conduct this study, semi-structured interviews were completed with ten current and former female Division I ISAs from six separate schools and seven countries. The results from this study suggest the core antecedents of the model - personal, inter-personal, perceptual, and cultural distance - were all still relevant. However, the factors included amongst these antecedents have shifted over time, with this study finding the importance of faculty and students (inter-personal) and nutrition (cultural distance) as significant factors in the transition of ISAs into US colleges. The results provide insights to administrators of US college athletics regarding how to help international student-athletes’ adaptation.